Dynamic linkages among financial development, economic growth, energy consumption, CO2 emissions and gross fixed capital formation patterns in Malaysia - Bekhet H.A.; Yasmin T.; Al-Smadi R.W. (Inderscience Publishers, 2023)
The aim of this research is to examine the dynamic relationship among financial development, economic growth, energy consumption, CO2 emissions and gross fixed capital formation in Malaysia. Time series data for the period 1970 to 2013, the ARDL model and multivariate Granger causality tests are used to determine the dynamic interrelationship among the study variables. The overall results show: 1) that all the variables are co-integrated during the study period; 2) a long-And short-run relationship existed between energy consumption and economic growth; 3) a long-run unidirectional Granger causality among the study variables is found; 4) there is a bidirectional causality running from economic growth to energy consumption and CO2 emission in the short run. It concludes that, with financial development and economic growth, effective energy policies need to cut the emissions level. The present study may guide the policymakers in formulating proper energy planning in Malaysia to attain future environmental targets while enhancing the financial perspective. 2017 Inderscience Enterprises Ltd.